2020
DOI: 10.1186/s12885-020-07311-4
|View full text |Cite
|
Sign up to set email alerts
|

Sulindac plus a phospholipid is effective for polyp reduction and safer than sulindac alone in a mouse model of colorectal cancer development

Abstract: Background Non-steroidal anti-inflammatory drugs (NSAIDs) such as aspirin and sulindac are effective for colorectal cancer prevention in humans and some animal models, but concerns over gastro-intestinal (GI) ulceration and bleeding limit their potential for chemopreventive use in broader populations. Recently, the combination of aspirin with a phospholipid, packaged as PL-ASA, was shown to reduce GI toxicity in a small clinical trial. However, these studies were done for relatively short periods of time. Sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Sulindac treatment resulted in a 58% reduction in polyp count, while sulindac-PC resulted in a 64% reduction. In addition, the researchers confirmed their hypothesis and showed that treatment with sulindac-PC minimized gastrointestinal ulceration compared to treatment with sulindac alone[ 123 ].…”
Section: Drmentioning
confidence: 87%
“…Sulindac treatment resulted in a 58% reduction in polyp count, while sulindac-PC resulted in a 64% reduction. In addition, the researchers confirmed their hypothesis and showed that treatment with sulindac-PC minimized gastrointestinal ulceration compared to treatment with sulindac alone[ 123 ].…”
Section: Drmentioning
confidence: 87%
“…11 Dietary polar lipids, including phosphatidylcholine, protect the gastric mucosa from inflammation in rodents. 30 A decrease in GlcCer levels weakens tight junctions in colonoids. 31 Dietary fungal GlcCer can reach the large intestine; therefore, it may play a role in membrane strengthening of the large intestine.…”
Section: ■ Discussionmentioning
confidence: 99%
“…One microliter of 6 M HCl and 200 μL of ethanol were added to 50 μL of mice plasma samples and then mixed for 1 min. The mixture was centrifuged twice at 20,000g for 30 Sphingolipids from mice freeze-dried fecal samples were extracted with ethanol as described. 23 The extract (0.40 mL) was added to 0.10 mL of 0.2 M HCl.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Comparatively, the anti-tumoral efficacy of the combination improved from NSAID monotherapy. In several in vivo studies, acetylsalicylic acid, indomethacin, and sulindac combined with PC expressed anti-tumoral activity against colon cancer in mice models [110,111].…”
Section: Combination Of Nsaids With Phosphatidylcholinementioning
confidence: 99%
“…acetylsalicylic acid, indomethacin, and sulindac combined with PC expressed ant moral activity against colon cancer in mice models [110,111].…”
Section: Combination Of Nsaids With Phosphatidylcholinementioning
confidence: 99%